‘Coyote Was Going There …’: The Role of Humor in Sacred Narrative and Performance - Kelley, Dennis (The international journal of religion and spirituality in society, 2013)
Many American Indian stories are tales of bawdy and risqué humor, as well as of great sacred gravity. That these two qualities, comic and sacred, are not considered mutually exclusive in American Indian traditional narratives has been suggested elsewhere (e.g. Andrews 2000; Aswell 2005; Bricker 1973; Lincoln 1993;). However, much of the treatment of the nature of humor in religion generally is situational and anecdotal rather than theoretical, for example, the ways in which ministers use jokes to convey Biblical themes in sermons or how humor and faith allow one to transcend adversity. My intent is to suggest that the categories "humor" and "sacred" co-define a genre of mythic narrative that plays an important role in American Indian religions, and that perhaps scholars might find this analysis helpful in the isolation of comic elements within the narratives of other of the world’s traditions. This theoretical direction, I will also herein suggest, can encompass much of what might be considered popular cultural expressions of humor, comic irony, and satire such as The Daily Show and the stand-up comedy of Louis C. K.